Penerapan Metode Drill Untuk Meningkatkan Hasil Belajar Siswa Kelas III MIN Sibuhuan - Sutan Botung; Harahap, Yulia Riska; Harahap, Nurhalimah (Yayasan Perguruan Kampus, 2025)
The purpose of this study was to determine the learning outcomes of mathematics students at MIN Sibuhuan in the application of the drill method. The type of research used is class action research (PTK), There are two sources of data in this study, namely 1. Primary data sources, namely data directly taken from the object of the researcher, namely students and teachers of class III. 2.This secondary data source comes from field data obtained from observations and interviews. The design of this research cycle has three cycles, namely Pre Cycle, Cycle I and Cycle II. Based on the results of research from improving student learning outcomes, it shows that in the pre-cycle student scores are still low, namely the average student score of 57.2. Students who completed as many as 15 students with a percentage of 51.7% and students who did not complete as many as 14 students with a percentage of 48.3%. Student learning outcomes in cycle I with an average score of 70.7 have begun to improve. Students who completed as many as 19 students with a percentage of 65.5% and students who did not complete as many as 10 students with a percentage of 34.5%. Meanwhile, student learning outcomes in cycle II student scores have increased with an average student score of 82.4. There were 26 students who were complete with a percentage of 89.7% and 3 students who were not complete. The results showed that the learning outcomes of students in Class III MIN Sibuhuan had implemented the learning process well. So it can be concluded that the learning outcomes of third grade students of MIN Sibuhuan can be improved by applying the drill method.